The Association between Religiosity and Work Ethics (Case of Study: State Organizations’ Employees in the City of Eghleed) - mansour haghighatian; vahid salehi (توسعه اجتماعی)
The work ethic of individuals is undoubtedly one the most important factors affecting social development, and one the most influential factors of individuals’ outlook and behavior, is religiosity. Those of stronger religious orientations are probably more inclined to observe ethical standards and have a more responsible attitude toward work and their duties. Therefore, the present article aims to study the relations between the level of religiosity and work ethic among Eghleed’s employees of governmental organizations. The research method employed was survey and the research instrument was questionnaire. The sample consisted of 300 workers of 42 government organizations who were selected a quota sampling technique. Gelock and Stark’s multidimensional model of religiosity was used. Research results showed that the level of both religiosity and work ethic among the respondents were above the medium. Correlations tests showed work ethic was significantly related to the dimensions of beliefs (r= 0.212), rituals (r = 0.338), experiential (r = 0.165), and consequential (r = 0.346). Path analysis showed that the path coefficient of consequential religiosity was 0.35, that of beliefs was 0.13, of rituals was 0.18, and of experiential was 0.02. All the independent variables could explain about 12 percent of the variance of the dependent variable.